The Effect of Education Using Audiovisual Media on Mothers' Knowledge about Japanese Encephalitis Immunization - Rosmaniah Rosmaniah; Rakhmawati Rakhmawati; Oon Fatonah Akbarini (Borneo Scientific Publishing, 2026)
Japanese Encephalitis (JE) is a viral disease and a leading cause of encephalitis worldwide. Immunization represents the most effective primary prevention strategy to protect individuals and reduce disease transmission. This study aimed to analyze the effect of audio-visual educational media on mothers’ knowledge regarding JE immunization in the working area of the Parit Timur Community Health Center. This quantitative study employed a pre-experimental design using a one-group pretest–posttest approach. A total of 66 mothers with toddlers were selected through accidental sampling. Data were analyzed using the Wilcoxon signed-rank test. The results demonstrated a significant improvement in mothers’ knowledge following the educational intervention. Prior to the intervention, knowledge scores ranged from 6 to 10, with a median of 8.00. After the intervention, scores increased to a range of 10 to 15, with a median of 14.00, indicating a median difference of 7.00. The Wilcoxon test yielded a p-value of <0.001, confirming a statistically significant difference between pretest and posttest scores. In conclusion, education using audio-visual media has a significant effect on improving mothers’ knowledge regarding JE immunization in the working area of the Parit Timur Community Health Center.